Welding for challenging environments : proceedings of the International Conference on Welding for Challenging Environments, Toronto, Ontario, Canada, 15-17 October 1985 (Pergamon Press, 1986)
Welding for Challenging Environments documents the proceedings of the International Conference on Welding for Challenging Environments held in Ontario, Canada on October 15-17, 1985.